Persepsi Pelaku Usaha Kecil dan Menengah tentang Tax Amnesty - Malia, Evi; baihaki, ach (Unversitas Islam Madura, 2016)
This Research aims to find out how big a review Participation Of Business Agent Micro, Small and Medium about Tax Amnesty. The data collection method using triangulation of data and methods of data analysis with way to reduce and then presents the data for the review verified. The Results is a business agent Micro, Small, and Medium Still tend Apathy for Tax Amnesty Program imposed by the Government That is because the level of awareness of business agent Dan Knowledge Against Taxation Still Really was low.